Association between overweight and central interleukin‐6 in a nonclinical adult population - Takako Enokida; Kotaro Hattori; Chiori Maeda; Takahiro Tomizawa; Hiroshi Kunugi (Neuropsychopharmacology Reports)
Abstract Aim Overweight is associated with low‐grade systemic inflammation. However, its effect on neuroinflammation remains unclear. We examined the possible association between overweight and neuroinflammation using cerebrospinal fluid (CSF) in a nonclinical adult population in Japan. Methods CSF and plasma levels of interleukin‐1β (IL‐1β), interleukin‐6 (IL‐6), tumor necrosis factor‐α (TNF‐α), plasma levels of C‐reactive protein (CRP), and leptin were measured in nonclinical adult participants (35 males and 34 females) who had no current or past history of neuropsychiatric diseases. We performed partial correlation analyses with sex and age as covariates between the body mass index (BMI) and the inflammatory markers and compared them between overweight and nonoverweight participants. Results The BMI significantly correlated with CSF levels of IL‐6 (rs = 0.32, p = 0.009), plasma levels of CRP (rs = 0.30, p = 0.016), IL‐1β (rs = 0.29, p = 0.019), IL‐6 (rs = 0.25, p = 0.042), TNF‐α (rs = 0.43, p < 0.001), and leptin (rs = 0.72, p < 0.001). Overweight participants (BMI ≧ 25) had significantly higher CSF levels of IL‐6 (p < 0.001), plasma levels of IL‐1β (p = 0.023), TNF‐α (p < 0.001), and leptin (p < 0.001) than the nonoverweight participants. Conclusion Overweight is associated with central IL‐6, a marker for neuroinflammation, as well as systemic inflammation markers, even in a nonclinical population.